Information literacy in the workplace: Perceptions and practices in academia / Iliasu Jinadu - Iliasu, Jinadu (2015)
The research established the avalanche of studies in information literacy (IL). Also, it identified that there had been a few of such studies in workplace IL because the existing IL models had their seemingly limitations to understand how information literacy evolve in the workplace especially among academics. Such limitations prompted a re-conceptualisation of IL and a subsequent design of a conceptual model- Workplace Information Literacy Model (WILM) – used as the conceptual framework for the study. The main aim of this research is to understand the activities and co-participation of academics in the workplace in Nigeria by exploring how IL evolves in the practices they engage in. The research took a practice approach to see, listen and learn from the academics what practice they engage in to prepare their undergraduates for the workplace; upon graduation. As a practice study, it explores insight into how the academics perceive information literacy, how they co-participate to interact with information in executing their routine tasks, and how their undergraduate students are prepared through such workplace practices. This therefore necessitated the study design of a qualitative case study. The study case was a College of Education. Nine (9) Heads of departments (HoDs) were selected on ‘purpose’ and they constituted the research participants. Rich data were collected through audio-recorded semi-structured in-depth interviews and un-obstructive observations. Aligning with the principles of case study, the study was able to pay particular attention to each individual participant in order to gain insight into how IL evolves in his or her practice. The study fulfilled all research ethics considerations while the participants were assured of their anonymity. The theoretical lens of ‘fit theory’ was employed to examine the participants as people in the know, who possess tacit knowledge, and co-participate to share such experiences. The rich data were analysed by coding in-vivo, constantly comparing the codes for similarities within and across data and eventually created significant themes that separated all insightful thoughts in the data. The findings show that the participants have different conceptions of information literacy while all the participants see IL as an ability to solve a problem. In addition, there were twenty-two practices which academics engage in as a response to a challenging information environment within which they work. The emergent themes of the study are: (1) Employee training and development, (2) Skill acquisition, (3) Assessment, (4) Information technology infrastructure, (5) Conceptions of information literacy, and (6) Administration. The research recommended that: (1) the domain of LIS should reconceptualise IL to look beyond the classroom for information literacy development, (2) governments in developing countries should improve information technology infrastructure to facilitate access to all media of information, and (3) IL skill developments efforts in the workplace should be encouraged by preparing undergraduates with industry-driven collaboration programmes. The research concluded that future research should: (1) Further test the conceptual model- WILM; and (2) Investigate how industry experts could share information literacy skills necessary for the novice employee.